(untitled) (Bangladesh Journal of Neurosurgery, 2020)
Spheno-orbital dysplasia is almost pathognomic for Neurofibromatosis type 1. Thereis proptosis and deviation of the eye ball medially. We present a case of a young girlwith neurofibromatosis type 1, who had pulsating exophthalmos of the right eye withdiplopia and severe dysplasia of the sphenoid boneand consecutive herniation of theright temporal lobe. She presented with pulsatile proptosis and deviation of the righteye ball to the right. Her x-ray skull showed widening of the orbit. Her MRI scanshowed an arachnoid cyst behind her right eye ball. We had operated on her andreconstructed the right sphenoid greater wing with titanium mesh and duroplastywith G-patch. This had improved her proptosis and deviation of the eye ball. Bang. J Neurosurgery 2020; 9(2): 156-161